2001
DOI: 10.1002/path.1023
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinicopathological features and karyotype in 100 cartilaginous and chordoid tumours. A report from the Chromosomes and Morphology (CHAMP) Collaborative Study Group

Abstract: The evaluation of chondroid lesions requires full integration of clinical, radiographic, and pathological data; tumour typing is often a challenge for the diagnostic pathologist. Although a variety of chromosomal abnormalities have been documented in chondroid lesions, the potential usefulness of cytogenetic analysis remains unclear. This study has critically reviewed and analysed 117 karyotyped samples from 100 patients with cartilaginous and chordoid tumours. Cases were selected based on successful chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…In the latter case, a breakpoint occurred in the proximal 6q13 region, most likely outside COL12A1. By reviewing the given probe map sequence, as reported by Yasuda et al, 9 we discovered discrepancies between the initially reported size and the recently revised size. As the length of BAC RP11-209D8 is not 10,206 bp but 166,681 bp, there is an overlap of 48,892 bp between the distal and proximal probe.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the latter case, a breakpoint occurred in the proximal 6q13 region, most likely outside COL12A1. By reviewing the given probe map sequence, as reported by Yasuda et al, 9 we discovered discrepancies between the initially reported size and the recently revised size. As the length of BAC RP11-209D8 is not 10,206 bp but 166,681 bp, there is an overlap of 48,892 bp between the distal and proximal probe.…”
Section: Discussionmentioning
confidence: 95%
“…† Already reported. 9 N, normal; NP, not performed; SA, split apart; SA/CO, split apart and co-localization; EG, extra green signal without increased centromeric signal (partial trisomy); HD, hemizygous deletion loss of both green and red signal for one allele.…”
Section: Evaluation Of Rearrangements In the Identified Breakpoints (mentioning
confidence: 99%
“…Several histological subtypes have been described; classical chordoma, which is the most common entity, chondroid chordoma, featuring regions resembling cartilage, and so-called 'dedifferentiated' chordoma, a rare subtype showing high-grade features. Histologically, chordomas are composed of physaliphorous cells expressing a particular low molecular weight cytokeratin pattern embedded in a mucomyxoid background (Mertens et al, 1994;Hazelbag et al, 1996;Dalpra et al, 1999;Scheil et al, 2001;Tallini et al, 2002). Clinically, chordomas manifest as slowly growing, locally destructive lesions with a tendency to infiltrate into adjacent tissues.…”
mentioning
confidence: 99%
“…Recurrent chromosomal aberrations in chordomas, identified using G-banding, metaphase comparative genomic hybridisation (mCGH), and fluorescence in situ hybridisation (FISH), include loss of the entire or parts of chromosomes 3, 4, 10, 13, and 18; loss or rearrangement of 1p and 9p; and gain of chromosome 7 (Sawyer et al, 2001;Scheil et al, 2001;Tallini et al, 2002;Kuzniacka et al, 2004;Brandal et al, 2005). However, neither by mCGH nor cytogenetics has any consistent structural chromosome aberration been detected.…”
mentioning
confidence: 99%
“…Indeed, a variety of chromosomal abnormalities and gene mutations can occur in CS, especially with high tumoral grade. 4 These abnormalities often comprise 12q13 amplification, the region harboring the p53 inhibitor MDM2 and cyclin-dependent kinase 4 (CDK4), but also 9p21 deletion. This chromosomal region includes the CDKN2A locus, coding for p16 INK4A and p14 ARF , which ensures a link between the RB and p53 pathways.…”
mentioning
confidence: 99%